УМОВИ ЕФЕКТИВНОГО ФУНКЦІОНУВАННЯ СИМБІОТИЧНОЇ СИСТЕМИ ЛЮПИН – ВRADYRHIZOBIUM SP. (LUPINUS) - Горбань , В.П. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2011)
The influence of some biogenic and abiogenic factors on the functioning of symbiotic system lupine – nodule bacteria was examined. The role of plants and nodule bacteria at the microbe-plant interaction was covered.